A Novel Homozygote Pathogenic Variant in the DIAPH1 Gene Associated With Seizures, Cortical Blindness, and Microcephaly Syndrome (SCBMS): Report of a Family and Literature Review - Emran Esmaeilzadeh; Sajjad Biglari; Meysam Mosallaei; Hamid Reza Khorram Khorshid; Hassan Vahidnezhad; Mohammad Amin Tabatabaiefar (Molecular Genetics & Genomic Medicine)
ABSTRACT Objective Mammalian Diaphanous‐Related Formin (mDia1), which is encoded by the DIAPH1 gene, serves as essential for the regulation of cell morphology and cytoskeletal organization. The role of DIAPH1 in brain development has been extensively established. This study aims to evaluate the clinical, neuroradiological, and genetic characteristics of patients with DIAPH1‐related disease and determine probable genotype–phenotype relationships. Methods In the current study, exome sequencing was performed to identify the genetic basis of the clinical presentation in an Iranian 7‐year‐old boy. Validation of the detected variant was done by Sanger sequencing. Furthermore, we performed a comprehensive review of the literature. Results Here, we detected a novel homozygous c.1285C> T (p.Gln429*) pathogenic variant in the patient. In silico analysis with prediction software tools identified this variant as a probable source of damage. Twenty cases from seven studies were found after a review of the literature. The patients' main symptoms were a developmental delay, microcephaly, and seizures. The mean age of onset for patients in the group of 20 patients with a known age of onset was 2.3 months (SD = 1.6). Of the variants identified, c.2769del, c.684+1G>A, and c.2332C> T were identified in 72% of the patients. Conclusion Considering the variant's position in the gene and the encoding protein, a pathogenic effect is predicted for the variant. So, the patient's clinical manifestation is probably caused by this pathogenic variant. Moreover, by studying clinical manifestations in all molecularly confirmed reported cases, provided a comprehensive overview of clinical presentation, and attempted to find a genotype–phenotype correlation.